Exploring challenges and perceptions in the learning environment: an online qualitative study of medical students - Mohammed Almansour; Fatmah Almoayad (BMC Medical Education, 2024)
Abstract Background The teaching and learning environment (TLE) in medical schools is critical for shaping the outcomes and competencies of graduates. Research on TLE has highlighted its influence on student learning approaches and outcomes, yet gaps remain, particularly in qualitative insights, especially in Saudi Arabian contexts. This study aims to explore the students’ experiences and perceptions of the TLE in a new medical college. Methods This qualitative study consisted of a total of five focus group discussions (3consequtive sessions for male group and two for female group) conducted virtually using the Zoom videoconferencing application. All the discussion sessions took place during a lockdown because of the COVID-19 pandemic between December 2020 and February 2021. Each session lasted for 45–60 min. Each group was formed of 4–5 students from different academic levels in the Majmaah medical school, which was established 10 years ago and is located in a small city. After “verbatim transcription” of the sessions was made, a framework thematic analysis of the data was performed using the NVivo software. Results The study results revealed that various elements, such as educational content, faculty roles, and personal factors, collectively influenced the students’ educational experiences. The students valued educational relevance and autonomous decision-making. The multifunctional role of faculty as mentors, evaluators, and resource providers was considered essential in enhancing academic experiences. Additionally, there was an evident need to improve the physical learning environment and facilities to adapt to emerging educational needs. These results align with existing literature, emphasizing the integration of theory and practice and the significant impact of faculty roles in academic experiences. Conclusion The findings suggest that medical colleges should involve students more in decision-making related to their education and ensure the practical relevance of the educational content. Establishing open communication channels between students and faculty who act as mentors and evaluators is also essential. Furthermore, enhancing supportive infrastructures, such as mental health and financial services, and promoting extracurricular activities are crucial for fostering a more effective and nurturing learning environment.